A descriptive study to assess the quality of life of reproductive system cancer patients during their follow up period - Pappachan C, Binsha; Thomas, Shine (International Journal of Nursing Research, 2023)
Background: Reproductive system cancer is a group of cancers which occurs when abnormal cells grow in an uncontrolled way. The comprehensive global cancer statistics from the International Agency for Research on Cancer indicate that gynecologic cancers accounted for 19% of the 5.1 million estimated new cancer cases, 2.9 million cancer deaths and 13 million 5-year prevalent cancer cases among women in the world in 2002. In India 3, 70,000 suffer annually and 2, 00,000 die every year. The diagnosis of cancer and the exhaustive treatment regime have a major impact on various aspects of life of patients which in turn affect their quality of life. Thus we planned to assess the quality of life among the survivors of reproductive system cancer during their follow up period. Objectives: To determine the quality of life among the reproductive system cancer patients during follow up period and find the association between the quality of reproductive system cancer patients with their selected demographic variables. Methods: A Descriptive study design was used for the present study. The sample consisted of 60 subjects suffering from reproductive system cancers. The subjects were mainly selected from the oncology OPD (Out Patient department) of the Father Muller Medical College Hospital. The tools used were baseline data and the quality of life questionnaire. The data was analyzed using descriptive and inferential statistics. Results: Majority (56.66%) of them had good quality of life during their follow up period. The overall mean quality of life was found to be 85.883 (SD 12.151) Fisher’s exact test reveals that there is no significant association between quality of life and selected demographic variables such as age, religion, education, occupation, marital status and family income. Conclusion: After conducting the study the result was found that, majority of the patient are having good quality of life. It was found that none of the patients are having poor quality of life.